2015
DOI: 10.1186/s12891-015-0656-5
|View full text |Cite
|
Sign up to set email alerts
|

Press-fit fixation using autologous bone in the tibial canal causes less enlargement of bone tunnel diameter in ACL reconstruction - a CT scan analysis three months postoperatively

Abstract: BackgroundBone tunnel enlargement is a phenomenon present in all anterior cruciate ligament (ACL)- reconstruction techniques. It was hypothesized that press-fit fixation using a free autograft bone plug reduces the overall tunnel size in the tibial tunnel.MethodsIn a prospective cohort study twelve patients who underwent primary ACL reconstruction using an autologous quadriceps tendon graft and adding a free bone block for press-fit fixation (PF) in the tibial tunnel were matched to twelve patients who underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 45 publications
2
22
0
3
Order By: Relevance
“…Ideal bone-to-bone healing is achieved when bone blocks are fixed with press-fit techniques, 12 additionally avoiding bony defects or potential tunnel widening. 13 Surgical techniques for and clinical results of press-fit and implant-free ACL reconstruction have been previously published, and interest in biologically more advantageous ACL reconstruction clearly exists. 4 Still, press-fit fixation of an ACL graft can be a challenging and time-consuming procedure, leading to low clinical acceptance.…”
Section: Biological Benefits and Press-fit Techniquementioning
confidence: 99%
“…Ideal bone-to-bone healing is achieved when bone blocks are fixed with press-fit techniques, 12 additionally avoiding bony defects or potential tunnel widening. 13 Surgical techniques for and clinical results of press-fit and implant-free ACL reconstruction have been previously published, and interest in biologically more advantageous ACL reconstruction clearly exists. 4 Still, press-fit fixation of an ACL graft can be a challenging and time-consuming procedure, leading to low clinical acceptance.…”
Section: Biological Benefits and Press-fit Techniquementioning
confidence: 99%
“…КТ сразу после операции не выполняли, а сравнивали полученные результаты с известными диаметрами из протоколов операций всех пациентов. Связано это с доказанным соответствием диаметра сверла, используемого во время хирургического вмешательства, и результатов измерений по КТ, проведенных на следующий день после него [7,15].…”
Section: материал и методыunclassified
“…Множество проведенных биомеханических и клинических исследований подтвердили, что прочность и жесткость подвесных кортикальных фиксаторов и трансплантата из одного сухожилия подколенной ямки являются достаточными и безопасными для восстановления ПКС [1,6,13,14]. Однако существует мнение, что именно этот вид фиксации трансплантата является причиной расширения костных каналов и возникновения осложнений в послеоперационном периоде [15,16]. Так A. E. Weber и соавт.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Afterwards, several authors reported their experience with this surgical technique [ 4 8 ]. Advantages of the press-fit fixation include direct bone-to-bone healing, accelerated rehabilitation, absence of hardware related complications or allergic reactions, less costs and the ease of revision procedures since there is no metal removal or tunnel enlargement [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%